Laserballoon and Cryoballoon Pulmonary Vein Isolation in Persistent and Longstanding Persistent Atrial Fibrillation. Issue 10 (30th August 2016) - STÖCKIGT, FLORIAN; KOHLMANN, ANNIKA T.; LINHART, MARKUS; NICKENIG, GEORG; ANDRIÉ, RENÉ P.; BEIERT, THOMAS; SCHRICKEL, JAN W.
Abstract : Background: Visually guided laserballoon (LB) ablation has recently been introduced for pulmonary vein (PV) isolation (PVI). We analyzed efficacy and safety results of the newly introduced LB ablation technique in patients with persistent and longstanding persistent atrial fibrillation (AF), and compared this with an established standard method using the cryoballoon (CB). Methods: A total of 35 patients with symptomatic persistent AF underwent LB ablation and were followed‐up for 1 year. Results were compared to 35 patients who underwent CB ablation at the same institution and case matched for age, sex, CHA2 DS2 ‐VASc score, and left atrial volume. Results: Complete isolation of all PVs was achieved in 68.6% in the LB and 97.1% in the CB group (P < 0.01). No significant differences were found for AF‐free survival after 12 months in the complete cohort of all patients (LB: 53.3% vs CB: 70.4%; P = n.s.) and after excluding patients without complete PVI (LB: 57.8% vs CB: 72.5%; P = n.s.). LB ablation resulted in longer procedure (158.5 ± 37.9 minutes vs 110.9 ± 26.5 minutes; P < 0.01) and fluoroscopy durations (28.4 ± 11.1 minutes vs 23.5 ± 9.4 minutes; P = 0.04.), and a trend toward more major complications (14.3% vs 2.9%; P = n.s.). Procedure durations and complications declined over time and were level with CB‐treated patients when reaching the last quartile of the LB patients. Conclusion: PVI in patients with persistent AF using the LB or the CB resulted in comparable success rates. Initial prolongations in procedure and safety parameters as a result of a learning curve effect for the LB have to be considered before starting to use this technique.